Negative electrode material, preparation method thereof and lithium ion battery

By constructing a copper-based compound coating on the graphite surface, the problem of insufficient flexibility and elasticity of the SEI layer in lithium-ion batteries is solved, the electrochemical performance and stability of the negative electrode material of lithium-ion batteries is improved, and more efficient lithium-ion is achieved Conductive and electrochemical properties.

CN119170758APending Publication Date: 2024-12-20CHONGQING INNOVATION CENTER OF BEIJING INSTITUTE OF TECHNOLOGY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410915228.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-09
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The SEI layer manually constructed in the prior art cannot have high ionic conductivity while reducing the desolvation performance, it is not flexible enough, has a low elastic modulus, and cannot accommodate large volume expansion, resulting in the negative electrode material of lithium-ion battery. Poor electrochemical performance.

Method used

The copper-based compound coating layer is constructed on the graphite surface. By mixing the non-metal element-containing precursor, the copper-containing precursor and graphite under vacuum, a uniform copper-based compound coating layer is formed, thereby improving the structural strength of the SEI film and the negative electrode material. conductivity.

Benefits of technology

It improves the chemical stability and structural stability of the negative electrode material, enhances the lithium ion conduction ability and electrochemical performance, alleviates the lithium evolution phenomenon, inhibits the growth of lithium dendrites, and improves the magnification and cycling performance of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170758A_ABST
    Figure CN119170758A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to a negative electrode material, a preparation method thereof and a lithium ion battery. The negative electrode material comprises graphite and a copper nitride coating layer attached to the surface of the graphite; wherein on the basis of the total mass of the negative electrode material, the content of the graphite is 5-15 wt%, and the content of the copper element is 1-10 wt%. The graphite is used as a raw material to be mixed with the non-metallic element-containing precursor and the copper-containing precursor, and the uniform coating layer containing the copper-based compound is constructed on the surface of the graphite, so that the obtained negative electrode material has high chemical stability and high structural stability, and the lithium ion conductivity and the electrochemical performance of the negative electrode material are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a negative electrode material and a preparation method thereof, and a lithium ion battery. Background Art

[0002] Since the commercialization of lithium-ion batteries in the 1990s, lithium-ion batteries have been widely used in portable electronic devices and electric vehicles, changing the modern lifestyle. Due to its low cost and good electrochemical reversibility, graphite has achieved widespread success in the field of lithium-ion battery anode materials. However, the poor rate performance of graphite limits its application in lithium-ion battery fast charging scenarios. Therefore, it is necessary to improve the fast charging and discharging capabilities of graphite anode materials.

[0003] In order to solve the above problems, the current strategies mainly include modification of graphite materials, coating (such as coating polymers, metal oxides, etc. on graphite), artificial construction of SEI protective layer, solid electrolytes and other methods.

[0004] CN117613211A discloses an Al2O3 coated graphite negative electrode material and its preparation method and application. The negative electrode material is a core-shell structure, including an Al2O3 shell and a spherical graphite core. The outer wall of the spherical graphite core is fitted with the inner wall of the Al2O3 shell, and discrete pores are maintained between the core and shell. The method can coat a uniform Al2O3 nanosheet / nanosphere layer on the graphite surface, and the capacity and first efficiency of the coated material are significantly improved.

[0005] CN114864916A discloses a niobium pentoxide-coated graphite composite negative electrode material, wherein the mass proportion of niobium pentoxide is 1-15wt%, and niobium pentoxide forms a uniformly distributed coating layer on the graphite negative electrode material, and the graphite negative electrode material is a spherical particle of 5-15μm. The method forms T-niobium pentoxide by coating niobium pentoxide on the graphite material and then sintering it, thereby effectively reducing the interface impedance and improving the cycle stability and fast charging ability of the graphite negative electrode material.

[0006] The above methods modify the graphite negative electrode to generate metal oxides coated on the graphite surface to prepare a composite negative electrode material. Although it can improve the electrochemical performance of the battery to a certain extent, these strategies do not fundamentally solve the growth problem of lithium dendrites and the infinite volume expansion caused by "mainless" deposition; or the constructed coating layer cannot construct a high-performance SEI layer, and the battery performance decreases rapidly during the cycle.

[0007] “M Wu, Z Wen, Y Liu, X Wang, L Huang. Electrochemical behaviors of a Li3Nmodified Li metal electrode in secondary lithium batteries. Journal of Power Sources, 196 (2011) 8091-8097” (Wu Min et al., Electrochemical behaviors of a Li3N modified lithium metal electrode in secondary lithium batteries. Journal of Energy, 196 (2011) 8091-8097) successfully prepared a layer of Li3N film on the surface of lithium metal at room temperature through the direct reaction of Li and N2 gas. A complete SEI film was artificially constructed at the electrode electrolyte interface through Li3N modification. The characterization results showed that the Li3N protective film has high stability in the electrolyte, its structure is tight and dense, and its thickness exceeds 159.4nm, which is much larger than the thickness of the natural SEI film formed on the original lithium surface. The SEI film is very effective in preventing the corrosion of lithium electrodes in liquid electrolytes, thereby reducing the resistance of the lithium|electrolyte interface and making the average short distance for lithium ions to diffuse from the electrolyte to the lithium surface reach 3.16×10 -3 cm.

[0008] The artificially constructed SEI layer is not very effective in improving the poor rate performance and long cycle performance of graphite, reducing the desolvation energy of lithium ions, and increasing the lithium ion transfer rate. It contains more organic components and fewer inorganic components, and cannot take all these indicators into account. Secondly, the artificially constructed SEI layer reported so far is usually unable to have high ionic conductivity while reducing the desolvation energy. It is not flexible enough, has a low elastic modulus, and cannot accommodate large volume expansion, resulting in the electrochemical performance of the coated electrode material being unsatisfactory.

[0009] Therefore, there is an urgent need to develop a negative electrode material with high chemical stability and structural stability, which can alleviate the problem of performance degradation of graphite negative electrode materials due to volume expansion during lithiation, thereby improving the electrochemical performance of the negative electrode material. Summary of the invention

[0010] The purpose of the present invention is to overcome the problems in the prior art that the artificially constructed SEI layer cannot have high ionic conductivity while reducing desolvation performance, is not flexible enough, has a low elastic modulus, cannot accommodate large volume expansion, and leads to poor electrochemical performance of the electrode material, and to provide a negative electrode material and a preparation method thereof and a lithium ion battery.

[0011] In order to achieve the above object, the present invention provides a negative electrode material in a first aspect, wherein the negative electrode material comprises graphite and a coating layer attached to the surface of the graphite;

[0012] Wherein, the coating layer includes a copper-based compound.

[0013] A second aspect of the present invention provides a method for preparing a negative electrode material, wherein the method comprises the following steps:

[0014] (1) Under vacuum conditions, a non-metallic element-containing precursor, a copper-containing precursor, and graphite are first mixed to obtain a mixture;

[0015] (2) The mixture is subjected to a second mixing, washing, and drying process to obtain a negative electrode material.

[0016] The third aspect of the present invention provides a negative electrode material prepared by the method of the present invention.

[0017] A fourth aspect of the present invention provides a lithium ion battery, wherein the lithium ion battery comprises the negative electrode material described in the present invention.

[0018] Through the above technical scheme, the present invention achieves the following beneficial technical effects: the present invention uses graphite as a raw material and mixes it with a non-metallic element precursor and a copper-containing precursor to construct a uniform coating layer of copper-based compounds on the graphite surface, thereby increasing the conductivity of the negative electrode and improving the structural strength of the SEI film, so that the negative electrode material has both high chemical stability and high structural stability, effectively improving the lithium ion conductivity of the negative electrode material and the electrochemical performance of the negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Schematic diagram of the particle structure of negative electrode material A1 in Example 1.

[0020] Figure 2 The first week charge and discharge curves of negative electrode materials A1 and B1 in Example 1 and Comparative Example 1, respectively, in an ester-based electrolyte, in a voltage window of 0.01V-1.5V, and at a current density of 0.1C (1C=200mAh / g).

[0021] Figure 3 This is the cycle curve of the ball-milled graphite in Example 1 in an ester-based electrolyte at a current density of 0.1C (1C=200mAh / g) in a voltage window of 0.01V-1.5V.

[0022] Figure 4 This is the cycle curve of the ball-milled graphite in Comparative Example 1 in an ester-based electrolyte at a current density of 0.1C (1C=200mAh / g) in a voltage window of 0.01V-1.5V.

[0023] Figure 5 The rate cycle curves are obtained when the ball-milled graphite in Example 1 is cycled in an ester-based electrolyte at a current density of 0.1C, 0.2C, 0.5C, and 1C (1C=200mAh / g) in the order of current density in a voltage window of 0.01V-1.5V.

[0024] Figure 6 The negative electrode materials A1, A6 and A7 in Example 1, Example 6 and Example 7 are respectively cycled for 300 cycles in an ester-based electrolyte at a current density of 1C (1C=200mAh / g) in a voltage window of 0.01V-1.5V.

[0025] Figure 7 The first week charge and discharge curves of negative electrode materials A1, A6 and A7 in Example 1, Example 6 and Example 7 respectively in ester-based electrolyte at a current density of 0.1C (1C=200mAh / g) in a voltage window of 0.01V-1.5V.

[0026] Figure 8 The rate cycle curves of the negative electrode material A1 in Example 1 obtained in an ester-based electrolyte at current densities of 0.1C, 0.2C, 0.5C, and 1C (1C=200mAh / g) in a voltage window of 0.01V-1.5V.

[0027] Fig. 9 This is a scanning electron microscope (SEM) image of the negative electrode material A1 in Example 1 combined with the EDS image of the Cu element K edge.

[0028] Fig.10 This is a scanning electron microscope (SEM) image of the negative electrode material A1 in Example 1 combined with the EDS image of the K edge of the C element.

[0029] Fig.11 This is a scanning electron microscope (SEM) image of the negative electrode material A1 in Example 1 combined with the EDS image of the N element K edge.

[0030] Fig.12 This is a scanning electron microscope (SEM) image of the negative electrode material A1 in Example 1 combined with an EDS image of the K-edge of the O element.

[0031] Fig.13 The negative electrode materials A1, B2 and B3 in Example 1, Comparative Example 2 and Comparative Example 3 are respectively cycled for 300 cycles in an ester-based electrolyte at a current density of 1C (1C=200mAh / g) in a voltage window of 0.01V-1.5V.

[0032] Fig.14 This is a scanning electron microscope (SEM) image of the ball-milled graphite in Comparative Example 1. DETAILED DESCRIPTION

[0033] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0034] A first aspect of the present invention provides a negative electrode material, wherein the negative electrode material comprises graphite and a coating layer attached to the surface of the graphite;

[0035] Wherein, the coating layer includes a copper-based compound.

[0036] According to some embodiments of the present invention, based on the total mass of the negative electrode material, the content of the graphite is 5-15wt%, and the content of the copper element is 1-10wt%.

[0037] In the present invention, the contents of graphite and copper in the negative electrode material can be measured by atomic absorption spectroscopy (AAS), and the instrument model is ContrAA 700 atomic absorption spectrometer.

[0038] The negative electrode material in the present invention includes graphite and a coating layer containing a copper-based compound attached to the surface of the graphite. If the copper content in the coating layer of the negative electrode material is too little, the negative electrode material cannot form a good conductive network during the pre-lithiation process; if the copper content in the coating layer of the negative electrode material is too much, the load of the coating layer will increase, and the porosity of the negative electrode material will increase, thereby affecting the electrochemical performance of the negative electrode material. When the copper content in the coating layer of the negative electrode material meets the above-mentioned limited range, it can reduce the desolvation ability of lithium ions on the SEI surface, improve the reaction activity, and reduce the activation energy, thereby further improving the electrochemical performance and structural stability of the negative electrode material; it can effectively reduce the lithium precipitation phenomenon, inhibit the growth of lithium dendrites, and improve the long-cycle performance of the electrode during the cycle process.

[0039] According to some embodiments of the present invention, the copper-based compound is selected from at least one of copper nitride, copper phosphate and copper sulfide, and is preferably copper nitride.

[0040] According to some embodiments of the present invention, the conductivity of the negative electrode material is 2×10 -5 -1.5×10 - 3 cm / S, tap density is 1.5-2.2g / cm 3 , porosity is 20%-40%, specific surface area is 6-12m 2 / g, particle size is 8-25μm.

[0041] In the present invention, the conductivity, tap density, porosity, specific surface area and particle size of the negative electrode material are measured by direct measurement, vibration method, density method, BET specific surface area method and ultrasonic method, respectively.

[0042] A second aspect of the present invention provides a method for preparing a negative electrode material, wherein the method comprises the following steps:

[0043] (1) Under vacuum conditions, a non-metallic element-containing precursor, a copper-containing precursor, and graphite are first mixed to obtain a mixture;

[0044] (2) The mixture is subjected to a second mixing, washing, and drying process to obtain a negative electrode material.

[0045] According to some embodiments of the present invention, the graphite has a particle size of 8-25 μm and a specific surface area of ​​5-10 m 2 / g.

[0046] In the present invention, the structural defects in the graphite can provide additional lithium storage sites, thereby improving the lithium storage capacity of the graphite, increasing the charge and discharge capacity, and extending the service life of the battery.

[0047] In the present invention, the graphite meeting the above requirements can be commercially available, or can be prepared by spheroidizing flake graphite or natural graphite.

[0048] Preferably, the particle size of the flake graphite or natural graphite is 0.12-0.15 mm.

[0049] Preferably, the conditions for the ball milling treatment include: the diameter of the grinding balls is 150-200 mm, the ball-to-material ratio is (6-10):1, the ball milling speed is 100-500 rpm, and the time is 3-10 hours.

[0050] In the present invention, the grinding balls used for ball milling are not particularly limited, and any material commonly used in the art can be used. For example, stainless steel grinding balls can be used for ball milling.

[0051] In the present invention, the conditions of the ball milling process affect the number of structural defects formed in the graphite. When the conditions of the ball milling process meet the above-mentioned limited range, the flake graphite or natural graphite can be fully ground, the particle size of the flake graphite or natural graphite can be reduced, and its specific surface area can be effectively increased. At the same time, a large number of structural defects are introduced, and the structural defects in the graphite can provide more Li + The sites embedded in graphite particles accelerate the lithium insertion process, especially the initial lithiation stage, thereby reducing polarization and increasing Li + The migration rate on the SEI film can improve the electrochemical performance of the negative electrode material.

[0052] According to some embodiments of the present invention, the non-metallic element-containing precursor is selected from at least one of a nitrogen-containing precursor, a phosphorus-containing precursor and a sulfur-containing precursor, and is preferably a nitrogen-containing precursor.

[0053] More preferably, the nitrogen-containing precursor is selected from at least one of benzylamine, aniline and cyclohexylamine.

[0054] According to some embodiments of the present invention, the copper-containing precursor is selected from at least one of copper methoxide, copper methylate and copper ethylate.

[0055] In the present invention, the types of nitrogen-containing precursors and copper-containing precursors will affect the types of by-products in the negative electrode material, making the washing process in the negative electrode material more complicated. When the nitrogen-containing precursors and copper-containing precursors are of the types specified above, the generation of by-products in the preparation process of the negative electrode material can be reduced, thereby simplifying the washing process.

[0056] According to some embodiments of the present invention, the mass ratio of the nitrogen-containing precursor, the copper-containing precursor and the ball-milled graphite is 1:(10-15):(1-5).

[0057] According to some embodiments of the present invention, the vacuum degree of the vacuum condition is -20 MPa to 15 MPa.

[0058] According to some embodiments of the present invention, the first mixing conditions include: a rotation speed of 1500-2000 rpm and a time of 10-40 min.

[0059] According to some embodiments of the present invention, the second mixing conditions include: temperature of 100-300° C. and time of 10-60 min.

[0060] In the present invention, preferably, the second mixing is carried out in an oil bath, and a magnetic stirrer may be used for stirring in order to allow the reactants to fully contact each other.

[0061] According to some embodiments of the present invention, the washing method comprises: washing the mixture with an organic solvent.

[0062] Preferably, the organic solvent is at least one selected from hexane, toluene and pentane.

[0063] In the present invention, the purpose of washing is to remove impurities in the mixture.

[0064] According to some embodiments of the present invention, the conditions for the drying treatment include: a temperature of 80-120° C. and a time of 8-12 h.

[0065] In the present invention, the drying process is carried out in an inert gas, preferably, the inert gas is selected from nitrogen and / or argon.

[0066] In the present invention, preferably, a mechanical ball milling method is used to modify flake graphite or natural graphite by ball milling, thereby reducing the particle size of graphite, increasing the specific surface area, and introducing a large number of structural defects; then a certain amount of nitrogen-containing precursor and copper-containing precursor are added, and ultrasonic stirring is performed to uniformly disperse the materials; and through subsequent oil bath heating and magnetic stirring steps, a uniform copper nitride coating layer is constructed on the graphite surface to obtain a negative electrode material of copper nitride-coated ball-milled graphite. The negative electrode material prepared by the present invention is used as a lithium ion battery, and the coated copper nitride layer is reduced to a lithium nitride layer during the cycle process. The formed lithium nitride layer has a high elastic modulus, which can alleviate the performance degradation of the negative electrode material caused by electrode perforation caused by the volume expansion of graphite during the lithiation process; the lithium ion transmission rate at the SEI interface is improved, and the rapid transmission of ions / electrons is ensured, thereby improving the rate performance and cycle performance of the negative electrode material; at the same time, the copper nitride coating layer forms a lithium nitride layer through circulation, which increases the proportion of inorganic components (such as Li3N) in the SEI film, can reduce the desolvation ability of lithium ions on the SEI surface, improve the reaction activity, reduce the activation energy, and further improve the chemical and structural stability.

[0067] In the present invention, further, during the cycle of the negative electrode material, when the copper nitride coating layer reacts with lithium ions, the copper nitride is reduced to lithium nitride, accompanied by the precipitation of copper element, thereby forming a Cu / Li3N nanocomposite material with a porous nano conductive network structure on the surface of the ball-milled graphite, which not only improves the conductivity of the negative electrode material, but more importantly improves the uniformity of the current density distribution, effectively reduces the lithium precipitation phenomenon, inhibits the growth of lithium dendrites, and improves the long cycle performance of the electrode during the cycle process; copper has higher chemical stability and structural strength, which makes the coating layer have the characteristics of high chemical stability and high structural stability at the same time, effectively improving the lithium ion conductivity and electrochemical performance of the negative electrode material.

[0068] The third aspect of the present invention provides a negative electrode material prepared by the method of the present invention.

[0069] A fourth aspect of the present invention provides a lithium ion battery, wherein the lithium ion battery comprises the negative electrode material described in the present invention.

[0070] According to a particularly preferred embodiment of the present invention, a method for preparing a negative electrode material is provided, the method comprising the following steps:

[0071] (1) Under vacuum conditions, a non-metallic element-containing precursor, a copper-containing precursor, and graphite are first mixed to obtain a mixture;

[0072] (2) subjecting the mixture to a second mixing, washing, and drying process to obtain a negative electrode material;

[0073] Among them, the particle size of graphite is 8-25μm, and the specific surface area is 5-10m 2 / g;

[0074] Wherein, the mass ratio of the non-metallic element-containing precursor, the copper-containing precursor and the graphite is 1:(10-15):(1-5);

[0075] Wherein, the vacuum degree of the vacuum condition is -20MPa to -15MPa;

[0076] The first mixing conditions include: a rotation speed of 1500-2000 rpm and a time of 10-40 min;

[0077] Wherein, the second mixing conditions include: temperature of 100-300°C and time of 10-60min;

[0078] The drying conditions include: a temperature of 80-120°C and a time of 8-12h;

[0079] The graphite content in the negative electrode material is 5-15wt%, and the copper content is 1-10wt%;

[0080] The conductivity of the negative electrode material is 2×10 -5 -1.5×10 -3 cm / S, tap density is 1.5-2.2g / cm 3 , porosity is 20%-40%, specific surface area is 6-12m 2 / g, particle size is 8-25μm.

[0081] The present invention will be described in detail below through examples.

[0082] The particle size of ball-milled graphite and negative electrode material was measured by ultrasonic method.

[0083] The specific surface areas of ball-milled graphite and negative electrode materials were determined using the BET specific surface area method.

[0084] The electrical conductivity, tap density and porosity of the negative electrode material were determined by direct measurement, vibration method and density method, respectively.

[0085] Unless otherwise specified, raw materials were commercially available.

[0086] Example 1

[0087] (1) adding 1 g of flake graphite (particle size of 0.12 nm) and stainless steel grinding balls into a ball mill for ball milling to obtain ball-milled graphite powder;

[0088] The ball milling conditions include: the diameter of the stainless steel grinding balls is 5 mm, the ball-to-material ratio is 10:1, the ball milling speed is 500 rpm, and the time is 5 h;

[0089] Among them, the particle size of ball-milled graphite powder is 20 μm and the specific surface area is 10 m 2 / g;

[0090] (2) In a glove box, copper methoxide, benzylamine and ball-milled graphite powder were added into a glass bottle in a mass ratio of 10:1:1 and mixed by ultrasonic stirring to obtain a mixture;

[0091] The conditions for ultrasonic stirring and mixing include: a rotation speed of 2000 rpm and a time of 0.5 h;

[0092] (3) The mixture was removed from the glove box and immediately placed in an oil bath at 150°C with magnetic stirring for 20 min. After keeping warm, it was cooled to 25°C to obtain the target solution.

[0093] (4) The target solution obtained in step (3) was washed three times with hexane, and the solid mixture collected by centrifugation was placed in an oven at 80° C. and dried for 12 h to obtain the negative electrode material A1 (denoted as Gr@Cu3N);

[0094] The A1 particles were observed by TEM characterization, and it can be seen that the A1 particles are a coated core-shell structure, such as Figure 1 As shown, the copper nitride coating is attached to the graphite surface;

[0095] Among them, the content of graphite in the negative electrode material A1 is 8.33wt% and the content of copper element is 5.05wt%;

[0096] Among them, the conductivity of negative electrode material A1 is 6×10 -3 cm / S, tap density is 2.1g / cm 3 , porosity is 21%, specific surface area is 9.5m 2 / g, particle size is 20μm.

[0097] Example 2

[0098] (1) adding 0.8 g of flake graphite (particle size of 0.15 nm) and stainless steel grinding balls into a ball mill for ball milling to obtain ball-milled graphite;

[0099] The conditions of ball milling treatment include: the diameter of the stainless steel grinding ball is 5 mm, the ball-to-material ratio is 8:1, the ball milling speed is 300 rpm, and the time is 7 h;

[0100] Among them, the particle size of ball-milled graphite is 20 μm and the specific surface area is 10 m 2 / g;

[0101] (2) In a glove box, copper methoxide, benzylamine and ball-milled graphite were added into a glass bottle in a mass ratio of 13:1:3 and mixed by ultrasonic stirring to obtain a mixture;

[0102] The conditions for ultrasonic stirring and mixing include: a rotation speed of 2000 rpm and a time of 0.5 h;

[0103] (3) The mixture was removed from the glove box and immediately placed in an oil bath at 200°C with magnetic stirring for 60 min. After keeping warm, it was cooled to 25°C to obtain the target solution.

[0104] (4) The target solution obtained in step (3) was washed three times with hexane, and the solid mixture collected by centrifugation was placed in an oven at 100° C. and dried for 10 h to obtain negative electrode material A2;

[0105] Among them, the conductivity of negative electrode material A2 is 2×10 -3 cm / S, tap density is 1.6g / cm 3 , porosity is 25%, specific surface area is 8.2m 2 / g, particle size is 18μm.

[0106] Example 3

[0107] (1) adding 0.8 g of flake graphite (particle size of 0.15 nm) and stainless steel grinding balls into a ball mill for ball milling to obtain ball-milled graphite;

[0108] The ball milling conditions include: the diameter of the stainless steel grinding balls is 5 mm, the ball-to-material ratio is 8:1, the ball milling speed is 100 rpm, and the time is 10 h;

[0109] Among them, the particle size of ball-milled graphite is 20 μm and the specific surface area is 10 m 2 / g;

[0110] (2) In a glove box, methyl copper, benzylamine and ball-milled graphite were added into a glass bottle in a mass ratio of 15:1:5 and mixed by ultrasonic stirring to obtain a mixture;

[0111] The conditions for ultrasonic stirring and mixing include: a rotation speed of 2000 rpm and a time of 1 h;

[0112] (3) The mixture was removed from the glove box and immediately placed in an oil bath at 300°C with magnetic stirring for 30 min. After keeping warm, it was cooled to 25°C to obtain the target solution.

[0113] (4) The target solution obtained in step (3) was washed three times with hexane, and the solid mixture collected by centrifugation was placed in an oven at 100° C. and dried for 10 h to obtain negative electrode material A3;

[0114] Among them, the conductivity of negative electrode material A3 is 3×10 -3 cm / S, tap density is 2.2g / cm 3 , porosity is 22%, specific surface area is 8m 2 / g, particle size is 21μm.

[0115] Example 4

[0116] According to the method of Example 1, except that the mass ratio of copper methoxide, benzylamine and ball-milled graphite is 20:1:1, to obtain negative electrode material A4;

[0117] Among them, the content of graphite in the negative electrode material A4 is 4.5wt% and the content of copper element is 45.8wt%;

[0118] Among them, the conductivity of negative electrode material A4 is 1.2×10 -3 cm / S, tap density is 1.6g / cm 3 , porosity is 30%, specific surface area is 6m 2 / g, particle size is 9μm.

[0119] Example 5

[0120] The method of Example 1 is followed, except that the ball-to-material ratio is 5:1, to obtain negative electrode material A5;

[0121] Among them, the conductivity of negative electrode material A5 is 1.5×10 -3 cm / S, tap density of 1.5g / cm3, porosity of 35%, specific surface area of ​​5m 2 / g, particle size is 18μm.

[0122] Example 6

[0123] According to the method of Example 1, except that the nitrogen-containing precursor is replaced with sodium phosphate to obtain negative electrode material A6;

[0124] Among them, the coating layer in the negative electrode material A6 is copper phosphate;

[0125] Among them, the conductivity of the negative electrode material A6 is 4×10 -4 cm / S, tap density is 1.8g / cm 3 , porosity is 38%, specific surface area is 6m 2 / g, particle size is 10μm.

[0126] Example 7

[0127] According to the method of Example 1, except that the nitrogen-containing precursor is replaced with sodium sulfide to obtain negative electrode material A7;

[0128] Among them, the coating layer in the negative electrode material A7 is copper sulfide;

[0129] Among them, the conductivity of the negative electrode material A7 is 4×10 -4 cm / S, tap density is 2g / cm 3 , porosity is 32%, specific surface area is 8m 2 / g, particle size is 23μm.

[0130] Comparative Example 1

[0131] (1) adding 1 g of flake graphite (particle size 0.12 nm) and stainless steel grinding balls into a ball mill for ball milling to obtain ball-milled graphite;

[0132] The ball milling conditions include: the diameter of the stainless steel grinding balls is 5 mm, the ball-to-material ratio is 10:1, the ball milling speed is 500 rpm, and the time is 5 h;

[0133] Among them, the particle size of ball-milled graphite is 20 μm and the specific surface area is 10 m 2 / g;

[0134] (2) The ball-milled graphite powder was placed in an oven at 80°C and dried for 12 h to obtain the negative electrode material B1 (denoted as Gr@Cu3N);

[0135] Among them, the conductivity of the negative electrode material B1 is 8×10 -5 cm / S, tap density is 1.5g / cm 3 , porosity is 26%, specific surface area is 8.5m 2 / g, particle size is 15μm.

[0136] Comparative Example 2

[0137] The negative electrode material B2 (referred to as flake graphite @Al2O3) was prepared by the method of Example 1 described in CN117613211A;

[0138] Among them, the conductivity of the negative electrode material B2 is 2×10 -4 cm / S, tap density is 1.8g / cm 3 , porosity is 34%, specific surface area is 9m 2 / g, particle size is 18μm.

[0139] Comparative Example 3

[0140] According to the method of Example 1, except that the copper-containing precursor is replaced with zinc methoxide to obtain negative electrode material B3;

[0141] Among them, the coating layer in the negative electrode material B3 is zinc nitride;

[0142] Among them, the conductivity of the negative electrode material B3 is 8×10 -4 cm / S, tap density is 1.6g / cm 3 , porosity is 28%, specific surface area is 6.4m 2 / g, particle size is 22μm.

[0143] Test Example 1

[0144] The negative electrode materials A1 and B1 in Example 1 and Comparative Example 1 were tested by scanning electron microscope (SEM), and the results are as follows: Figure 9-14 .

[0145] Test Example 2

[0146] The negative electrode materials A1, A6, A7 and B1-B3 in Example 1, Example 6, Example 7 and Comparative Examples 1-3 were assembled into button batteries, and then the electrochemical performance was tested. The results are shown in Figure 2-8 and Fig.13 .

[0147] The assembly method of the button battery includes: mixing the negative electrode material, Super P and PVDF (mass fraction 5%) in a mass ratio of 8:1:1, coating the obtained slurry on aluminum foil to make a positive electrode sheet, using a metal lithium sheet as the negative electrode, Cleard2500 as the diaphragm, and LB315 solution as the electrolyte (wherein the solvent is diethyl carbonate and ethylene carbonate, and the solute is LiPF6), assembling the button battery in an argon glove box, and conducting an electrochemical performance test after standing for 8 hours.

[0148] The electrochemical performance test was carried out on a Wuhan Blue Electric CT2001A battery tester. The test charge and discharge voltage was 0.01V-1.5V, and the charge and discharge rate was 0.1C-10C (1C current density was 300mAh / g).

[0149] Figure 2 The first-week charge-discharge curves of negative electrode materials A1 and B1 in Example 1 and Comparative Example 1, respectively, in an ester-based electrolyte, in a voltage window of 0.01V-1.5V, and at a current density of 0.1C (1C = 200mAh / g). Figure 2 It can be seen that the reversible capacity of the negative electrode material A1 (Gr@Cu3N) in Example 1 is 338 mAh / g, and the first-week coulombic efficiency is 81%; the reversible capacity of the negative electrode material B1 (Gr) in Comparative Example 1 is 300 mAh / g, and the first-week coulombic efficiency is 65%.

[0150] Figure 3The cycle curve of the ball-milled graphite in Example 1 in an ester-based electrolyte at a current density of 0.1C (1C = 200 mAh / g) in a voltage window of 0.01V-1.5V. Figure 3 It can be seen that the specific capacity of the ball-milled graphite in Example 1 is maintained at 365 mAh / g after 55 cycles.

[0151] Figure 4 The cycle curve of the ball-milled graphite in comparative example 1 in an ester-based electrolyte at a current density of 0.1C (1C = 200 mAh / g) in a voltage window of 0.01V-1.5V. Figure 4 It can be seen that in Comparative Example 1, the reversible capacity of the ball-milled graphite in the ester-based electrolyte is 299 mAh / g, and the coulombic efficiency in the first week is only 61%.

[0152] Figure 5 The current density multiplier cycle curve of the ball-milled graphite in Example 1 in an ester-based electrolyte at a voltage window of 0.01V-1.5V in the order of 0.1C, 0.2C, 0.5C, and 1C (1C = 200mAh / g). Figure 5 It can be seen that the ball-milled graphite in Example 1 has poor rate performance, the capacity is not high and decreases rapidly.

[0153] Figure 6 The negative electrode materials A1, A6 and A7 in Example 1, Example 6 and Example 7 were respectively cycled for 300 cycles in an ester-based electrolyte at a current density of 1C (1C = 200 mAh / g) in a voltage window of 0.01V-1.5V. Figure 6 It can be seen that the capacity of negative electrode material A1 in Example 1 after 300 cycles is significantly higher than that of negative electrode materials A6 and A7 in Examples 6 and 7, indicating that the long cycle performance of negative electrode material A1 in Example 1 is excellent.

[0154] Figure 7 The first-week charge-discharge curves of negative electrode materials A1, A6 and A7 in Examples 1, 6 and 7 in ester-based electrolyte at a current density of 0.1C (1C = 200 mAh / g) in a voltage window of 0.01V-1.5V. Figure 7 It can be seen that the first-cycle reversible capacity of the negative electrode material A1 in Example 1 is higher than that of the negative electrode materials A6 and A7 in Examples 6 and 7, indicating that the initial charge and discharge performance of the negative electrode material A1 in Example 1 is relatively excellent.

[0155] Figure 8 The cycle curves of negative electrode material A1 in Example 1 in an ester-based electrolyte at a current density of 0.1C, 0.2C, 0.5C, and 1C (1C = 200 mAh / g) in a voltage window of 0.01V-1.5V. Figure 8It can be seen that the rate performance of the negative electrode material A1 (Gr@Cu3N) in Example 1 is significantly better than that of the ball-milled graphite body, and the capacity is higher and decreases slowly.

[0156] Fig. 9 This is a scanning electron microscope (SEM) image of the negative electrode material A1 in Example 1 combined with the EDS image of the Cu element K edge. Fig. 9 It can be seen that the Cu element in the negative electrode material A1 (Gr@Cu3N) in Example 1 is uniformly distributed.

[0157] Fig.10 This is a scanning electron microscope (SEM) image of the negative electrode material A1 in Example 1 combined with the EDS image of the K edge of the C element. Fig.10 It can be seen that the C element in the negative electrode material A1 (Gr@Cu3N) in Example 1 is uniformly distributed.

[0158] Fig.11 This is a scanning electron microscope (SEM) image of the negative electrode material A1 in Example 1 combined with the EDS image of the N element K edge. Fig.11 It can be seen that the negative electrode material A1 (Gr@Cu3N) in Example 1 presents a graphite particle morphology, a relatively smooth surface, and randomly distributed particles.

[0159] Fig.12 This is a scanning electron microscope (SEM) image of the negative electrode material A1 in Example 1 combined with an EDS image of the K edge of the O element. Fig.12 It can be seen that the negative electrode material A1 (Gr@Cu3N) in Example 1 has a uniform distribution of O elements.

[0160] Fig.13 The negative electrode materials A1, B2 and B3 in Example 1, Comparative Example 2 and Comparative Example 3 were respectively cycled for 300 cycles in an ester-based electrolyte at a current density of 1C (1C = 200 mAh / g) in a voltage window of 0.01V-1.5V. Fig.13 It can be seen that the negative electrode material A1 in Example 1 has a higher capacity than the negative electrode materials B2 and B3 in Comparative Examples 2 and 3 after 300 cycles, indicating that the negative electrode material A1 in Example 1 has better long cycle performance.

[0161] Fig.14 Scanning electron microscope (SEM) image of graphite in Comparative Example 1. Fig.14 It can be seen that the ball-milled graphite in Comparative Example 1 has an uneven surface, is very rough, and has many surface defects.

[0162] In summary, the negative electrode material of the present invention has excellent lithium ion conductivity and electrochemical performance.

[0163] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A negative electrode material, characterized in that: The negative electrode material includes graphite and a coating layer attached to the surface of the graphite; Wherein, the coating layer includes a copper-based compound.

2. The negative electrode material according to claim 1, wherein Based on the total mass of the negative electrode material, the content of the graphite is 5-15wt%, and the content of the copper element is 1-10wt%; And / or, the copper-based compound is selected from at least one of copper nitride, copper phosphate and copper sulfide, preferably copper nitride.

3. The negative electrode material according to claim 1 or 2, wherein The conductivity of the negative electrode material is 2×10 -5 -1.5×10 -3 cm / S, tap density is 1.5-2.2g / cm 3 , porosity is 20%-40%, specific surface area is 6-12m 2 / g, particle size is 8-25μm.

4. A method for preparing a negative electrode material, characterized in that: The method comprises the following steps: (1) Under vacuum conditions, a non-metallic element-containing precursor, a copper-containing precursor, and graphite are first mixed to obtain a mixture; (2) The mixture is subjected to a second mixing, washing, and drying process to obtain a negative electrode material.

5. The method according to claim 4, wherein: The graphite has a particle size of 8-25 μm and a specific surface area of ​​5-10 m 2 / g.

6. The method according to claim 4 or 5, wherein: The non-metallic element-containing precursor is selected from at least one of a nitrogen-containing precursor, a phosphorus-containing precursor and a sulfur-containing precursor, and is preferably a nitrogen-containing precursor; More preferably, the nitrogen-containing precursor is selected from at least one of benzylamine, aniline and cyclohexylamine; And / or, the copper-containing precursor is selected from at least one of copper methoxide, copper methylate and copper ethylate.

7. The method according to any one of claims 4 to 6, wherein: The mass ratio of the non-metallic element-containing precursor, the copper-containing precursor and the graphite is 1:(10-15):(1-5); And / or, the vacuum degree of the vacuum condition is -20MPa to -15MPa; And / or, the first mixing conditions include: a rotation speed of 1500-2000 rpm and a time of 10-40 min; And / or, the second mixing conditions include: temperature of 100-300° C. and time of 10-60 min.

8. The method according to any one of claims 4 to 7, wherein: The washing method comprises: washing the mixture with an organic solvent; Preferably, the organic solvent is selected from at least one of hexane, toluene and pentane; And / or, the drying treatment conditions include: temperature of 80-120° C. and time of 8-12 hours.

9. A negative electrode material obtained by the method according to any one of claims 4 to 8.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode material according to any one of claims 1-3 and 9.